Biogas : Clean Energy Access with Low-Cost Mitigation of Climate Change - Somanathan, E.; Bluffstone, Randall (World Bank, Washington, DC, 2015)
With data from the nearly 6,000 households in the Nepal Living Standards Survey of 2010–11, this paper finds that the mean reduction in household firewood collection associated with use of a biogas plant for cooking is about 1,100 kilograms per year from a mean of about 2,400 kilograms per year. This estimate is derived by comparing only households with and without biogas in the same village, thus effectively removing the influence of many potential confounders. Further controls for important determinants of firewood collection, such as household size, per capita consumption expenditure, cattle ownership, and unemployment are used to identify the effect of biogas adoption on firewood collection. Bounds on omitted variable bias are derived with the proportional selection assumption. The central estimate is much smaller than those in the previous literature, but is still large enough for the cost of adopting biogas to be significantly reduced via carbon offsets at a modest carbon price of $10 per ton of CO2e when using central estimates of emission factors and global warming potentials of pollutants taken from the scientific literature.